2020
DOI: 10.1088/1361-6455/abcb52
|View full text |Cite
|
Sign up to set email alerts
|

Electron impact single ionization of hydrogen molecule by twisted electron beam

Abstract: In this communication, we present the results of the five-fold differential cross-section (5DCS) and triple differential cross-section (TDCS) for the (e, 2e) process on molecular hydrogen (H2) by the plane wave and the twisted electron beam impact. The formalism is developed within the first Born approximation using the plane wave and the twisted wave for the incident electron beam. We describe the plane wave, Heitler–London type wave function, Coulomb wave for the scattered electron, the H2 molecular state, a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 64 publications
1
21
0
Order By: Relevance
“…By substituting the plane wave-function with the Bessel wave-function (equation (16) in equation( 3)), we obtain the twisted wave transition amplitude (T tw f i (κ, q)) in terms of the plane wave transition amplitude T f i (q) (equation ( 12)) as (in the frozen-core approximation) [45];…”
Section: B Twisted Electron Ionization Cross-sectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…By substituting the plane wave-function with the Bessel wave-function (equation (16) in equation( 3)), we obtain the twisted wave transition amplitude (T tw f i (κ, q)) in terms of the plane wave transition amplitude T f i (q) (equation ( 12)) as (in the frozen-core approximation) [45];…”
Section: B Twisted Electron Ionization Cross-sectionsmentioning
confidence: 99%
“…They also explored the influence of the twisted electron beam on the (e,2e) process on the H 2 molecule from the perspective of the 'Young-type' interference of the scattered waves emanating from the two atomic centers of the H 2 molecule. Their results found that the angular profile of the TDCS and FDCS depends on the OAM number, m, and the opening angle, θ p , of the incident twisted electron beam [45].…”
Section: Introductionmentioning
confidence: 99%
“…Inelastic collision of twisted electrons with atoms or molecules can also lead to impact ionization of atoms and molecules [156,157]. In these (e, 2e) processes, the incident vortex electron knocks out a secondary electron of much lower energy.…”
Section: Vortex States For Atomic Physicsmentioning
confidence: 99%
“…here, e − i , e − s , e − e , X and X + represents the incident, scattered, the ejected electron, the target atom and the ionized target respectively. The theory used here closely follows the approach used in our previous studies [39,40]. We have carried out the theoretical analysis in the framework of the first Born approximation.…”
Section: Theoretical Formalismmentioning
confidence: 99%
“…The study by showed the dependence of the Total Angular Momentum (TAM) number (m) and opening angle (θ p ) on the angular profile of the TDCS and spin asymmetry for the relativistic electron impact ionization of the heavy atomic targets [38]. Dhankhar et al investigated the influence of the OAM number 'm' and the opening angle θ p single ionization cross-sections of H 2 and H 2 O molecule by twisted electron waves independently [39,40].…”
Section: Introductionmentioning
confidence: 99%